Exclusivity and comprehensiveness of Law. Some reflections on the open nature of legal systems - Navarro, Pablo E. (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
This paper analyzes the possible meaning and plausibility of two well-known theses: exclusivity and comprehensiveness of law. According to the first, the positive norms exhaust the content of the law, while the second expresses that legal systems always provide an answer to justify a judicial decision. The theoretical framework chosen is the approach of contemporary legal positivism and, it is shown that, to a large extent, a positivistic interpretation of both above-mentioned theses depends on a distinction between the «global system», which is the set of norms valid at a certain moment T (i.e., the moment of the judicial decision that resolves a dispute) and the system of applicable norms. In turn, this distinction allows us to analyze the open nature of global systems from four different points of view: regulatory, logical, normative and interpretative. Finally, the consequences of these distinctions for the problem of judicial discretion are explored.
Keywords: legal gaps; judicial discretion; legal system; normative validity; applicability